2021
DOI: 10.3389/fonc.2021.733595
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glycolysis-Related lncRNAs and the Novel lncRNA WAC-AS1 Promotes Glycolysis and Tumor Progression in Hepatocellular Carcinoma

Abstract: BackgroundHigh glycolysis efficiency in tumor cells can promote tumor growth. lncRNAs play an important role in the proliferation, metabolism and migration of cancer cells, but their regulation of tumor glycolysis is currently not well researched.MethodsWe analyzed the co-expression of glycolysis-related genes and lncRNAs in The Cancer Genome Atlas (TCGA) database to screen glycolysis-related lncRNAs. Further prognostic analysis and differential expression analysis were performed. We further analyzed the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
(47 reference statements)
3
32
1
Order By: Relevance
“…It was proved that the overexpression of DNM3OS played a role in the development of ovarian cancer [ 44 ]. WAC-AS1, a competing endogenous RNA, has a great influence on the regulation of tumor glycolysis [ 45 ]. Additionally, the prognoses of glioma patients who had low WAC-AS1 expression were better than the high-expression group [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that the overexpression of DNM3OS played a role in the development of ovarian cancer [ 44 ]. WAC-AS1, a competing endogenous RNA, has a great influence on the regulation of tumor glycolysis [ 45 ]. Additionally, the prognoses of glioma patients who had low WAC-AS1 expression were better than the high-expression group [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00339, a highly expressed lncRNA in a Frontiers in Genetics frontiersin.org variety of malignant diseases, such as digestive system tumors, respiratory system tumors and nervous system tumors, is associated with the proliferation, motility and invasion of tumor cells (Wu Z. et al, 2022). WAC-AS1 could promote hepatocellular carcinoma through a glycolysis-related pathway (Xia et al, 2021). The function of lncRNA is reliant on cell environment and tissue specificity, which explains this seemingly paradoxical phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Through transcriptomic analysis, some studies have suggested that C2orf27A can affect the resistance of HCC cells to sorafenib through immune infiltration ( Yuan et al, 2021 ), which is consistent with our findings. MIR210HG can be used as a glycolysis-related lncRNA to influence the progression of HCC ( Xia et al, 2021 ). We plotted nomograms to predict 1-, 3-, and 5-year OS in HCC patients to intuitively use this predictive model.…”
Section: Discussionmentioning
confidence: 99%